AKUNTANSI LINGKUNGAN DAN AKUNTANSI MANAJEMEN LINGKUNGAN : SUATU KOMPONEN DASAR STRATEGI BISNIS - Yudhanta Sambharakreshna (InFestasi, 2009)
Environmental Accounting (EA) and EnvironmentalManagement Accounting (EMA) is a new tool for managers to identify,measure, evaluate and report environmental costs (including internal andexternal costs). The environmental costs have impacts to sustainabilityof company in business process. In this modern, management not onlyachieves financial performance (profitability objective) but also it resultsenvironmental performance to support going concern of company.Implication of environmental accounting and environmental managementaccounting in business strategy are providing environmental informationto help managers for determining environmental indicators as evaluationof performance (environmental performance), and techniques such asActivity-Based Costing system (ABC), Total Cost Assessment (TCA), FullCost Environmental Assessment (FCEA) and Life-Cycle Assessment (LCA)that are useful for managers to identify, evaluate, measure and reportcosts related environment to product in business process.This paper explains indicators of environment to be used in measuringperformance, techniques used in measuring environmental cost such asTCA, FCA/FCEA and LCA. Also, it will describes linking EnvironmentalAccounting (EA) and Environmental Management Accounting (EMA) tobusiness strategy.